2017
DOI: 10.18632/oncotarget.20761
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Echinococcus multilocularis and Echinococcus granulosus hydatid fluid proteome provides molecular strategies for specialized host-parasite interactions

Abstract: Alveolar and cystic echinococcoses, caused by the metacestodes of Echinococcus multilocularis and E. granulosus, are prevalent in several regions and invoke deleterious zoonotic helminthiases. Hydatid fluid (HF), which contains proteinaceous and non-proteinaceous secretions of the parasite- and host-derived components, critically affects the host-parasite interplay and disease progression. We conducted HF proteome profiling of fully mature E. multilocularis vesicle (nine months postinfection) and E. granulosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 43 publications
(64 reference statements)
1
27
2
Order By: Relevance
“…AgB8/1 has been reported as the most abundant subunit in E. granulosus AgB oligomer [36], and it is the AgB subunit consistently identified by MS based analysis of HF [8,14,37]. However, the detection and the abundance of AgB8/2 to 5 in HF is rather variable [8,9,14,37]. Also, the AgB subunits representation in HF vary among different Echinococcus species [14,38].…”
Section: Papilin Belongs To the Adamts (A Disintegrin-like And Metallmentioning
confidence: 99%
See 2 more Smart Citations
“…AgB8/1 has been reported as the most abundant subunit in E. granulosus AgB oligomer [36], and it is the AgB subunit consistently identified by MS based analysis of HF [8,14,37]. However, the detection and the abundance of AgB8/2 to 5 in HF is rather variable [8,9,14,37]. Also, the AgB subunits representation in HF vary among different Echinococcus species [14,38].…”
Section: Papilin Belongs To the Adamts (A Disintegrin-like And Metallmentioning
confidence: 99%
“…However, the detection and the abundance of AgB8/2 to 5 in HF is rather variable [8,9,14,37]. Also, the AgB subunits representation in HF vary among different Echinococcus species [14,38]. multilocularis [13,37,39].…”
Section: Papilin Belongs To the Adamts (A Disintegrin-like And Metallmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain a protein-by-protein characterization of PSEx, an extensive in silico study of its identified proteome was performed ( Table 2). Prediction of cellular localization showed a predominance (73%) of cytoplasmic proteins (42 in 57), followed by 11% characterized as mitochondrial 35,39 Abbreviations: aa, amino acid; IP, isoelectric point. ; MW, molecular weight; IP, isoelectric point.…”
Section: In Silico Psex Characterizationmentioning
confidence: 99%
“…2 The parasites can grow in two forms: unilocular cyst or cystic echinococcosis (CE) and multilocular cyst or alveolar echinococcosis (AE). 3 CE is the most common form of disease among nomadic area in which dogs play an important role in habitation. Echinococcus granulosus (E granulosus) can grow in every organ or body tissue and produce small cysts.…”
Section: Introductionmentioning
confidence: 99%